2020
DOI: 10.3390/cells9030643
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Translocation in Neurons after Ischemic Insult: Subcellular Localization in Mitochondria and Peroxisomes

Abstract: High mobility group box-1 (HMGB1), a nonhistone chromatin DNA-binding protein, is released from neurons into the extracellular space under ischemic, hemorrhagic, and traumatic insults. However, the details of the time-dependent translocation of HMGB1 and the subcellular localization of HMGB1 through the release process in neurons remain unclear. In the present study, we examined the subcellular localization of HMGB1 during translocation of HMGB1 in the cytosolic compartment using a middle cerebral artery occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Recently, Wang et al reported the subcellular localizations of HMGB1 in neurons after ischemic insults in adult rats 65 . They found that HMGB1 was co‐localized with mitochondria and peroxisomes in the cytosolic compartment when HMGB1 formed granular structures, suggesting a possible role for HMGB1 in energy metabolism of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al reported the subcellular localizations of HMGB1 in neurons after ischemic insults in adult rats 65 . They found that HMGB1 was co‐localized with mitochondria and peroxisomes in the cytosolic compartment when HMGB1 formed granular structures, suggesting a possible role for HMGB1 in energy metabolism of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that secretion-ready cytosolic HMGB1 is packed into a secretory lysosome or autophagosome and secreted via non-conventional secretion mechanisms, requiring a very complex, as yet unknown, packaging mechanism. Conversely, a recent article by Wang et al observed HMGB1 localization in mitochondria and peroxisome in neuron cells via electron microscopy and immunofluorescence, but not in lysosomes (121). In macrophages or macrophage lineages, the release of HMGB1 occurred through a lysosomal pathway after acetylation of the HMGB1 (16).…”
Section: Hmgb1 Secretion Kineticsmentioning
confidence: 91%
“…Recent work on the translocation of HMGB1 in neurons after ischemic insult indicated that the HMGB1 translocated from nuclei to cytoplasm was colocalized with mitochondria and peroxisomes [ 73 ] during the release process. Moreover, HMGB1 was colocalized with Drp-1, a protein involved in the fission of mitochondria, suggesting that HMGB1 also exerts cell-metabolism-modifying effects in these organelles during the translocation process [ 73 ].…”
Section: Stroke and Bbb Disruptionmentioning
confidence: 99%